2018
DOI: 10.3390/nano8040253
|View full text |Cite
|
Sign up to set email alerts
|

Increased Level of α2,6-Sialylated Glycans on HaCaT Cells Induced by Titanium Dioxide Nanoparticles under UV Radiation

Abstract: As one of the most widely used nanomaterials, the safety of nano-TiO2 for human beings has raised concern in recent years. Sialylation is an important glycosylation modification that plays a critical role in signal transduction, apoptosis, and tumor metastasis. The aim of this work was to investigate the cytotoxicity and phototoxicity of nano-TiO2 with different crystalline phases for human skin keratinocytes (HaCaT cells) under ultraviolet (UV) irradiation and detect sialic acid alterations. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The degree of photocytotoxicity and cell membrane damage depends greatly on the level of ROS generated. More recently, Ren et al also reported a similar finding on the phototoxicity of TiO 2 NPs in HaCaT cells under UV irradiation [329].…”
Section: Neat Tio 2 Npssupporting
confidence: 58%
“…The degree of photocytotoxicity and cell membrane damage depends greatly on the level of ROS generated. More recently, Ren et al also reported a similar finding on the phototoxicity of TiO 2 NPs in HaCaT cells under UV irradiation [329].…”
Section: Neat Tio 2 Npssupporting
confidence: 58%
“…The size of nano-TiO 2 used in the present study was 25 nm, the characterization of which has been described previously. 8 The crystalline composition was a mixture of rutile and anatase. From day 3 to 7, the cells were seeded in fibrin gels and imaged to evaluate 3D spheroid formation ( Figure 1A).…”
Section: Nano-tio 2 Under Uva Irradiation Cause Reduced Growth Of Mulmentioning
confidence: 99%
“…Nano-TiO 2 with photoreactivity under UVA irradiation induce significant cell damage, lipid peroxidation, and overexpression of glycans, which leads to phototoxic reactions. [6][7][8] Nano-TiO 2 induce normal liver cell apoptosis by triggering the production of a large amount of reactive oxygen species (ROS) under UVA irradiation, resulting in upregulation of the death receptor, Fas, and Bax. 1 Despite the plethora of research regarding the phototoxicity of nano-TiO 2 in vitro and in vivo, the acute toxicity of nano-TiO 2 and the underlying mechanisms remain a major concern in the assessment of nanotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of TiO2-NPs in sunscreens and cosmetics makes relevant the study of their potential toxicity and hazardous effects in human skin, since they are in close contact for long periods of time. Previous reports, have evaluated the cytotoxicity (Wright et al 2017), genotoxicity (Jaeger et al 2012) or metabolic effects (Tucci et al 2013;Ren et al 2018) of TiO2-NPs in human keratinocytes. However, a further evaluation to gain a deeper insight into the biomolecular mechanisms related to those observed effects have not yet been accomplished.…”
Section: Introductionmentioning
confidence: 99%